Uji pembebanan statik meja kerja kantor dengan konstruksi pen-lubang dan alur-isian - Bahtiar Rahmat; Taufik Ramadhan Fitrianto; Desy Mulyosari; Nurhanifah Nurhanifah; Siska Anggiriani; Anshah Silmi Afifah (Institut Seni Indonesia Yogyakarta, 2026)
An ergonomic work environment requires furniture to be compatible with the dimensions of the user's body in order to avoid musculoskeletal complaints and decreased productivity. A data-driven anthropometric design approach combined with structural simulation is a strategy to ensure both comfort and strength of the product. This study applies the Finite Element Method (FEM) to analyze the strength of a work table with a hole-and-groove construction before mass production. A combination of mahogany and plywood was chosen for cost efficiency, while the strength of the joints between components was the main focus of the evaluation. The simulation process included 3D modeling, material selection, boundary condition determination, loading in accordance with SNI 8781-2019, meshing, and analysis of results. The desk measured 1200×600×750 mm with four fixed support points on the legs. The results showed good structural performance in all tests. Stability and vertical strength tests showed that the stress and displacement were below the elastic limit of the material. Fatigue tests showed a damage level of only 1 percent, while drop tests resulted in a displacement of 1.55 mm without permanent deformation. Overall, the table design was deemed safe, stable, and suitable for production.